Creative/Cultural Industry – Opportunistic Barrier Evidence - Oliveira, Antonio Monteiro; Rua, Orlando Lima (Journal Of Exact Sciences and Technological Applications, 2021)
Based on the Owl interventions – Super Bock – Solid Dogma publicity agency, in this study we propose to describe and analyse the emergence of the opportunistic barrier within creative and cultural industry. We adopted a qualitative methodology and use photography as a research technique. The results allow us to conclude that the emergence of opportunistic behaviours results in the destruction of creativity rather than the creative destruction proposed by entrepreneurial action literature.